Improving the relationship between Muslims and Christians in Hausa land : an analytical study - Abubakar, Bashir Sani (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This humble research explored the attempts made by different quarters to bridge mutual mistrust, and to achieve peaceful and harmonious co-existence between Muslims and Christians in the Northern part of Nigeria. The essential principles on the basis of which peaceful co-existence and mutual understanding were established among the followers of different religions in northern Nigeria were evaluated in this study. The whole argument in this research is associates with many factors that may have contributed to the turbulent situation in northern Nigeria. They are ethnic, religious, political and economic. These main factors were studied and analysed in order to come out with the solutions that would prevent, or at least minimize conflict, and promote integration on the basis of solidarity, tolerance, and justice. Challenges and prosperity from these factors were then discussed. Moreover, issues related to dialogue and interfaith activities which both affect people's lives, and they can be useful in establishing a society that shares common concern on relaxation, compassion, and cooperation were also highlighted. These have been witnessed as one of the major unifying factor of the various ethnics in the northern part of the country. The study concluded that people have to relate to each other as a matter of necessity, as peace would only be realized if religious and ethnic groups respect each other, and understand their differences. Furthermore, both religious leaders should come up with strategies that help to prevent crises before they occur that involve encouraging dialogues among religious followers, and to explore solutions to the major challenges of coexistence of both religions. Moreover, the Nigerian Government should be more proactive in eliminating all the root causes of the ethnic and religious crisis in order to stop the perpetuation of violence, which claimed many innocent lives.